PROSES DIFUSI TEKNOLOGI KONSERVASI LAHAN KERING MELALUI PEMUKA PENDAPAT (OPINION LEADERS) DI KABUPATEN BANTUL - Raden Kunto Adi; Retno Setyowati (AGRITEXTS: Journal of Agricultural Extension, 2010)
The objectives of this research were (I). To know the diffution levels of the conservation technology, and (2). To know the role opinion leaders on the diffution process of dry land conservation technology. The methods of collecting the primary data has done with interview, with the sum of samples are 60 peoples. The data analysis used by the multiple linier regression analysis. The results of this research were (I). The diffution of the conservation, technology by farmers at high levels, and (2). The roles of opinion leader., which influence to diffution levels of the conservation technology are dissemination, linkage and mobilisators, ·and three of els independent variables were initiation, interest articulation, and overseer, were not influence to alffution levels of the conservation technology.